Economic and health aspects in times of quarantine for COVID 19 in the Peruvian population, year 2020.: Aspectos económicos y de salud en tiempos de cuarentena por COVID 19 en población peruana, año 2020. - Cuenca Jaque, Cintia Rosmeri; Osorio Tarrillo, Milagros Lucila; Pastor Ramos, José Leonardo; Peña Pasapera, Gloria del Pilar; Torres Vásquez, Lissette Estefany (Revista de la Facultad de Medicina Humana, 2020)
Objective: To identify the economic and health aspects in times of quarantine COVID 19 Peruvian population in 2020. Methods: The study had a quantitative approach, descriptive level and non-experimental design, with a sample of 1,064 Peruvians from all regions of Peru surveyed in the month of March to April of the year 2020. For the statistical analysis, the distribution of absolute and relative frequencies was used. Results: Regarding the economic situation, 57.3% refer that they have presented many or some economic problems to buy basic necessities, 69.8% say they have food today for less than seven days; 56.8% have enough money for less than two weeks. In addition, 79.5% reported have not been benefited with some bonus or subsidy status and 65.8% say that bonds are little or subsidies to acquire the basics. Regarding health aspects, 10.5% of those surveyed stated that some of the members of their household had symptoms; and 1.1% report that there is a confirmed carrier of COVID -19 in their family. 88.3% have altered the feeling generated by social isolation, and 56.4% have felt stress due to social isolation. Conclusion: In the end it is concluded that there are economic problems to buy food and medicine, that food is sufficient only for 7 days, money is only enough for two weeks, the bonds are few to acquire the basic and most of the family it has not been benefited by any bonus. And as regards health, most of them have a feeling altered by social isolation and they present stress from quarantine.